DmGEN, a novel RAD2 family endo-exonuclease from Drosophila melanogaster - Ishikawa, Gen (Oxford University Press, 2004)
A novel endo-exonuclease, DmGEN (Drosophila Melanogaster XPG-like endonuclease), was identified in D.melanogaster. DmGEN is composed of five exons and four introns, and the open reading frame encodes a predicted product of 726 amino acid residues with a molecular weight of 82.5 kDa and a pI of 5.36. The gene locus on Drosophila polytene chromosomes was detected at 64C9 on the left arm of chromosome 3 as a single site. The encoded protein showed a relatively high degree of sequence homology with the RAD2 nucleases, especially XPG. Although the XPG-N- and XPG-I-domains are highly conserved in sequence, locations of the domains are similar to those of FEN-1 and EXO-1, and the molecular weight of the protein is close to that of EXO-1. In vitro, DmGEN showed endonuclease and 3′–5′ exonuclease activities with both single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA), but the endonuclease action with dsDNA was quite specific: 5′–3′ exonuclease activity was found to occur with nicked DNA, while dsDNA was endonucleolytically cut at 3–4 bp from the 5′ end. Homologs are widely found in mammals and higher plants. The data suggest that DmGEN belongs to a new class of RAD2 nuclease.